A. R. Galloway. The autism of reason / trans. from Engl. Z. M. Neustroev - Z. M. Neustroev (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the key principles of François Laruelle’s non-philosophical project and analyzes it comparatively with the Kantian categories of a priori, a posteriori, analytical and synthetic. It discovers certain parallels between the a priori and transcendental account of non-philosophy, its theory of subjectivity and autistic perception of the real.